Effect of Er2O3 dopant on electrical and optical properties of potassium sodium niobate silicate glass-ceramics - Yongsiri,P. (Elsevier Limited, 2015)
© 2015 Elsevier Ltd. In this study, transparent glass-ceramics from potassium sodium niobate (KNN)-silicate glass system doped with erbium oxide (Er2O3) were successfully prepared by incorporation method. KNN was added in glass batches as heterogeneous nucleating agent. The KNN powder was mixed with SiO2 and Er2O3 dopant with KNN and Er2O3 content varied between 70-80 and 0.5-1.0mol%, respectively. Each batch was subsequently melted at 1300°C for 15min in a platinum crucible using an electric furnace. The quenched glasses were then subjected to heat treatment at various temperatures for 4h. XRD results showed that the prepared glass ceramics contained crystals of KNN solid solution. In contrary, dielectric constant (ε r) and dielectric loss (tanδ) were found to increase with increasing heat treatment temperature. Additionally, optical properties such as absorbance and energy band gap have been investigated.